2018
DOI: 10.1016/j.jns.2018.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Domain-specific characterisation of early cognitive impairment following spontaneous intracerebral haemorrhage

Abstract: Cognitive deficits after spontaneous intracerebral haemorrhage (ICH) are common and result in functional impairment, but few studies have examined deficits across cognitive domains in the subacute phase. This study aims to describe the cognitive profile following acute ICH and explore how cerebral amyloid angiopathy (CAA) may impact performance. We retrospectively reviewed 187 consecutive patients with ICH (mean age 58.9 years, 55.6% male) with available imaging and neuropsychological data (median 12 days afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 21 publications
1
35
0
Order By: Relevance
“…Three additional studies chose to selectively exclude patients that met the criteria for dementia but included patients with mild impairments, using preexisting dementia as a contributory factor for future deficits (12,23,28). The remaining studies [9 (28.1%)] either did not assess or report on preexisting CI (5,6,15,21,24,27,32,34,36).…”
Section: Post-ich Cognitive Impairment Over Time and Contributory Factorsmentioning
confidence: 99%
See 4 more Smart Citations
“…Three additional studies chose to selectively exclude patients that met the criteria for dementia but included patients with mild impairments, using preexisting dementia as a contributory factor for future deficits (12,23,28). The remaining studies [9 (28.1%)] either did not assess or report on preexisting CI (5,6,15,21,24,27,32,34,36).…”
Section: Post-ich Cognitive Impairment Over Time and Contributory Factorsmentioning
confidence: 99%
“…The three acute phase studies reported that 84.0% of ICH patients demonstrated impairment in one or more cognitive domain at 12 days post-stroke (5,16,31), with 65.0% showing impairment in two or more domains (5), 75.2% of patients impaired at 2 weeks (16) and 82.4% of patients showing 2+ domain impairment at 3 weeks (31). Of the 3 studies, 1 assessed for delirium before testing (41) and 2 assessed for disorders of consciousness and aphasia (16,31).…”
Section: Post-ich Cognitive Impairment Over Time and Contributory Factorsmentioning
confidence: 99%
See 3 more Smart Citations